Coparenting and relationship satisfaction in mothers: The moderating role of sociosexuality - Lamela, Diogo (2022)
This study explored the moderating efect of sociosexual orientation on the association between coparenting alliance/coparenting confict and relationship satisfaction in mothers in a romantic relationship. Sociosexuality is defned as a personality trait that refects the individual diference in willingness to engage in uncommitted sexual relations. The study examined a community sample of 635 Portuguese mothers with a monogamous heterosexual relationship. Data on coparenting, relationship satisfaction, and sociosexual orientation were collected. The results revealed the moderating efect of sociosexuality on the signifcant associations between both coparenting alliance and coparenting confict predicting relationship satisfaction. For the association between coparenting alliance and relationship satisfaction, mothers with a more restricted sociosexual orientation reported the highest levels of satisfaction when their coparenting alliance was high, but the lowest levels of satisfaction when coparenting alliance was low. For the association between coparenting confict and relationship satisfaction, mothers with a more restricted sociosexual orientation reported the highest levels of satisfaction when their coparenting confict was low, but the lowest levels when coparenting confict was high. Together, the results suggest that especially for women with a more restricted sociosexual orientation, coparenting quality explains signifcant interindividual variability in relationship satisfaction